The Acts of the Apostles - Munck Johannes; Munck, Johannes, 1904-1965; Albright, William Foxwell, 1891-1971; Mann, C. S. (Christopher Stephen), 1917- (Garden City, New York : Doubleday & Company, Inc., 1967)
The Anchor Bible Commentary is the collaborative effort of Protestant, Catholic, and Jewish scholars from around the world
The Acts of the Apostles and the Gospel of Luke -- The content of the Acts of the Apostles -- Luke's language and style -- The sources of Luke's two-part work -- The time of composition -- The purpose of Luke's work -- Primitive Jewish Christianity -- Paul's trial -- Luke's testimony -- The text of the Acts
Includes bibliographical references (pages lxxxviii-xc)
Marquis W. Brown Class of 1953 Memorial
Translated into English from the original ancient Greek
Keywords: Bible. -- Commentaries; Bible. -- Criticism, interpretation, etc; Reference works; Sacred works